An accurate and sensitive analytical strategy for the determination of palladium in aqueous samples: slotted quartz tube flame atomic absorption spectrometry with switchable liquid-liquid microextraction after preconcentration using a Schiff base ligand - Firat, Merve; Bakirdere, Emine Guelhan (SPRINGER, 2019)
This study presents a green analytical method for palladium determination by slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS) following switchable liquid-liquid microextraction (SLLME). Efficient extraction of palladium was facilitated by complexation with a Schiff base ligand, synthesized specifically for this study. A three-stage thorough optimization procedure was carried out to boost the absorbance output of palladium. Complex formation was the first stage, and parameters evaluated included buffer solution pH and amount, concentration of ligand, and mixing period. The amount of switchable solvent and concentration and amount of sodium hydroxide and acid amount were optimized in the second stage. Optimization of sample and fuel flow rates and SQT parameters completed the third stage of optimization, and all optimum parameters were used to determine analytical performance of the method. The method had a broad linear dynamic range, and the calibration plots showed good linearity with R-2 values greater than 0.9991. The limits of detection and quantification of the SLLME-SQT-FAAS method were 15 and 50g/L, respectively. The precision of the method, expressed as percent relative standard deviation, was below 9.0% for all measurements. Spiked recovery results performed for a palladium electroplating bath solution gave poor results when quantified against aqueous calibration standards. Matrix matching was therefore used to improve recovery results which ranged between 97 and 105% for four different spike concentrations.
Keywords: Palladium; FAAS; Switchable liquid-liquid microextraction; Slotted quartz tube; Schiff base; CLOUD POINT EXTRACTION; PHASE MICROEXTRACTION; ICP-MS; ONLINE SEPARATION; VAPOR GENERATION; WATER SAMPLES; TRACE LEVELS; CADMIUM; LEAD; CLASSIFICATION; Environmental Sciences & Ecology